Análise fitossociológica em formação ripária da floresta estacional semidecidual no sul do Brasil : rio Pirapó, Cruzeiro do Sul, PR. - Corino, Helverton Luís (2006)
A phytosociological study was made on the remaining riparian forest, located on the left bank of the Pirapó River (22°57'06"S; 52°02'40"W) . The research was carried out by using the point-centered-quarter method. Only individuals with a PBH ≥15 cm were included in the study. A total of 90 points were sampled in three different blocks, each one containing three parallel lines going along the river. The distance between the points was 10 meters. The floristic composition resulted in 72 species, embracing 58 genera and 28 families. The total density estimated was 1.375 individuals per hectare. Leguminosae and Myrtaceae were the families with the highest specific richness. The species considered the most important, regarding values (IV), were Gallesia integrifolia (Spreng.), Harms, Ruprechtia laxiflora Meisn., Campomanesia xanthocarpa (Cambess.) O. Berg, Diatenopteryx sorbifolia Radlk. and Tabebuia heptaphylla (Vell.) Toledo. The specific diversity, estimated by using Shannon index (H') was 3.81, whereas, the equability (J') was 0.88. Such values were above the average, if compared to the statistics on riparian forests of semi-deciduous seasonal forests covering the State of Paraná.